Relationship between Autoimmune Hemolytic Anemia and Covid-19 Infection: Literature Review - Agiratama, Nanda Putri; Sefrina, Linda Riski (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Background : The World Health Organization (WHO) determined that the world had been hit by a Global Health Emergency in January 2020 due to the spread of the 2019 Corona virus which spread rapidly in various countries and became a new pandemic threat. Several international studies reported that there were cases in patients with Covid-19 infection who were detected as having hemolytic anemia. Aim : The aim of this study was to determine whether there was a relationship between Covid-19 infection and the incidence of hemolytic anemia. The method used in this study is a literature review, namely collecting data from previous research from various sources related to a predetermined topic. Results :  The results of this study indicate that there are various cases of Covid-19 patients diagnosed with hemolytic anemia such as warm and cold autoimmune hemolytic anemia. Conclusion : Tests that can be done to detect hemolytic anemia include Coombs test, cold agglutinin titer, bilirubin, complete blood count, G6PD deficiency test, and haptoglobin. As a follow-up to Covid-19 patients with hemolytic anemia, appropriate and immediate treatment is needed according to their condition.